2018
DOI: 10.1016/j.rbmo.2017.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Luteal phase progesterone and oestradiol after ovarian stimulation: relation to response and prediction of pregnancy

Abstract: Research has focused on optimizing luteal phase support and endometrial receptivity in ovarian stimulation cycles. In this study, serial endocrine measurements were taken in 600 patients after a gonadotrophin-releasing hormone antagonist stimulation protocol. On the day of blastocyst transfer, serum progesterone and oestradiol were similar irrespective of a subsequent positive or negative pregnancy test (median 99 ng/ml versus 103 ng/ml for progesterone, respectively) or a subsequent live birth or pregnancy lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…In the current study, the final follicle count >11mm was found in the regression analysis to significantly reduce LBR in HR (> 18 follicles) when compared with poor and intermediate responders [OR: 0.10, 95% CI, 0.03-0.33] (Table 3), which is consistent with the findings reported by a recent study showing a steady reduction in LBR beyond twenty oocytes retrieved, presumably due to supraphysiological circulating steroids levels [35]. Besides, the present data show a significant correlation between the ovarian response and both preovulatory and midluteal P 4 levels (S1 Table ) suggesting that each follicle contributes to the pool of serum P 4 before ovulation triggering [20,36] as well as after oocyte retrieval [24,37]. Contrasting the preovulatory serum P 4 level, the current results suggest that the midluteal P 4 level is an independent factor associated with LB potential, and, interestingly, in a nonlinear pattern, [OR: 2.73 (1.29-5.78); p< 0.008] (Table 3).…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, the final follicle count >11mm was found in the regression analysis to significantly reduce LBR in HR (> 18 follicles) when compared with poor and intermediate responders [OR: 0.10, 95% CI, 0.03-0.33] (Table 3), which is consistent with the findings reported by a recent study showing a steady reduction in LBR beyond twenty oocytes retrieved, presumably due to supraphysiological circulating steroids levels [35]. Besides, the present data show a significant correlation between the ovarian response and both preovulatory and midluteal P 4 levels (S1 Table ) suggesting that each follicle contributes to the pool of serum P 4 before ovulation triggering [20,36] as well as after oocyte retrieval [24,37]. Contrasting the preovulatory serum P 4 level, the current results suggest that the midluteal P 4 level is an independent factor associated with LB potential, and, interestingly, in a nonlinear pattern, [OR: 2.73 (1.29-5.78); p< 0.008] (Table 3).…”
Section: Discussionsupporting
confidence: 92%
“…The correlation between serum P levels on the day of the pregnancy test and pregnancy outcome has been also studied in stimulated cycles, with contradictive results. While some authors suggest that serum P can have a predictive role (8,9), others could not find this association (10). The difficulty in these stimulated cycles relies on the fact that the endocrine profile depends on the ovarian response, type of trigger and luteal phase support (11)(12)(13)(14), and this could influence the interpretation of results.…”
Section: Discussionmentioning
confidence: 99%
“…Improvement in and individualization of COS regimens have been the subject of intensive research in the field of ART, and patient-tailored COS has now become the state of the art. In contrast, the luteal phase of fresh IVF cycles has received little attention, and studies focusing on luteal phase characteristics following hCG triggering are scarce and have yielded conflicting results [56][57][58][59]. Neither the updated Cochrane meta-analysis on LPS [7], nor the ESHRE guidelines [6] have included recommendations regarding patient monitoring during the luteal phase.…”
Section: Personalized Luteal Phase Supportmentioning
confidence: 99%